The Relationship Between Body Mass Index (BMI) and the Incidence of Preeclampsia Among Third-Trimester Pregnant Women at Tiron Public Health Center, Kediri Regency - Errina Febrianti; Koekoeh Hardjito; Rahajeng Siti Nur Rahmawati; Eny Sendra (Akademi Keperawatan Yarsi Samarinda, 2026)
Preeclampsia is a pregnancy complication and a leading cause of maternal morbidity and mortality worldwide. One risk factor often associated with preeclampsia is pre-pregnancy Body Mass Index (BMI). This study aimed to analyze the relationship between BMI and the incidence of preeclampsia among third-trimester pregnant women at the Tiron Public Health Center, Kediri Regency. A quantitative study with a cross-sectional design was conducted. The sample consisted of 44 third-trimester pregnant women selected through simple random sampling from a population of 77. Data were obtained from maternal and child health records, blood pressure measurements, and proteinuria examinations. Results showed that most respondents had a normal BMI (50%), followed by overweight (25%), obesity (15.9%), and underweight (9.1%). Preeclampsia was identified in only one respondent (2.27%), who was classified as overweight. Statistical analysis yielded a p-value (0.425) α >( 0,05) indicating no significant relationship between BMI and preeclampsia incidence. The absence of a significant association may be related to the predominance of normal BMI respondents and the identification of only one preeclampsia case.